OsSNDP4, a Sec14-nodulin Domain Protein, is Required for Pollen Development in Rice - Xu, Weitao; Peng, Xiaoqun; Li, Yiqi; Zeng, Xinhuang; Yan, Wei; Wang, Changjian; Wang, Cheng Rui; Chen, Shunquan; Xu, Chunjue; Tang, Xiaoyan (Rice (New York, N.Y.), 2024)
Pollen is encased in a robust wall that shields the male gametophyte from various stresses and aids in pollination. The pollen wall consists of gametophyte-derived intine and sporophyte-derived exine. The exine is mainly composed of sporopollenin, which is biopolymers of aliphatic lipids and phenolics. The process of exine formation has been the subject of extensive research, yet the underlying molecular mechanisms remain elusive. In this study, we identified a rice mutant of the OsSNDP4 gene that is impaired in pollen development. We demonstrated that OsSNDP4, a putative Sec14-nodulin domain protein, exhibits a preference for binding to phosphatidylinositol (3)-phosphate [PI(3)P], a lipid primarily found in endosomal and vacuolar membranes. The OsSNDP4 protein was detected in association with the endoplasmic reticulum (ER), vacuolar membranes, and the nucleus. OsSNDP4 expression was detected in all tested organs but was notably higher in anthers during exine development. Loss of OsSNDP4 function led to abnormal vacuole dynamics, inhibition in Ubisch body development, and premature degradation of cellular contents and organelles in the tapetal cells. Microspores from the ossndp4 mutant plant displayed abnormal exine formation, abnormal vacuole enlargement, and ultimately, pollen abortion. RNA-seq assay revealed that genes involved in the biosynthesis of fatty acid and secondary metabolites, the biosynthesis of lipid polymers, and exosome formation were enriched among the down-regulated genes in the mutant anthers, which correlated with the morphological defects observed in the mutant anthers. Base on these findings, we propose that OsSNDP4 regulates pollen development by binding to PI(3)P and influencing the dynamics of membrane systems. The involvement of membrane systems in the regulation of sporopollenin biosynthesis, Ubisch body formation, and exine formation provides a novel mechanism regulating pollen wall development.